Systematic Review of Library Service Accesibility using Artificial Intelligence: Features, Challenges, and Library Roles - Pipit Tunjungsari; Suprihatin, Suprihatin (Knowledge Garden: International Journal of Library Studies, 2024)
Libraries play a vital role in providing access to knowledge but face accessibility challenges for disabled usres. AI technology, like chatbots and text-to-speech, can ehnance library accessibility despite challenges such as funding and ethical concerns. This study explores AI’s use for navigation and training to improve library accessibility for disabled users. Using a systematic literature review of ScienceDirect articles from 2014-2024, the study examines AI technology features, impelentation challenges, and libraries’ roles in providing support. The analysis reveals that main AI features include speech-to-text, text-to-speech, and virtual assistants. Implementation challenges involve staff skill gaps, budget constraints, and ethical issues. Libraries play a crucial role in integrating AI, promoting AI literacy, and offering inclusive facilities. The implementation of AI technology is essential to improve accessibility through features like voice recognition, OCR, and touch-based interaction. However, challenges such as cost, infrastructure, staff training, and data security must be addressed. Libraries should focus on providing infrastructure, training, collaboration, evaluation, and promotion of services, as well as clear accessibility policies. AI implementation should prioritize solving technical, financial, and human resource challenges, while supporting collaboration with disability organizations and technology developers. Further research is needed to gauge the effectiveness, efficiency, and integration of AI for inclusive library services.